SiYGL2 Is Involved in the Regulation of Leaf Senescence and Photosystem II Efficiency in Setaria italica (L.) P. Beauv. - Zhang, Shuo; Zhi, Hui; Li, Wen; Shan, Jianguo; Tang, Chanjuan; Jia, Guanqing; Tang, Sha; Diao, Xianmin (Frontiers in Plant Science, 2018)
A yellow-green leaf mutant was isolated from EMS-mutagenized lines of Setaria italica variety Yugu1. Map-based cloning revealed the mutant gene is a homolog of Arabidopsis thaliana AtEGY1. EGY1 (Ethylene-dependent Gravitropism-deficient and Yellow-green 1) is an ATP-independent metalloprotease that is required for chloroplast development, photosystem protein accumulation, hypocotyl gravitropism, leaf senescence, and ABA signal response in Arabidopsis thaliana. However, the function of EGY1 in monocotyledonous C4 plants has not yet been described. The siygl2 mutant is phenotypically characterized by chlorotic organs, premature senescence, and damaged PS II function. Sequence comparisons of the AtEGY1 and SiYGL2 proteins reveals the potential for SiYGL2 to encode a partially functional protein. Phenotypic characterization and gene expression analysis suggested that SiYGL2 participates in the regulation of chlorophyll content, leaf senescence progression, and PS II function. Additionally, our research will contribute to further characterization of the mechanisms regulating leaf senescence and photosynthesis in S. italica, and in C4 plants in general.